Towards Rahmatan lil 'Alamin Economy (Analysis of Ukhuwah Islamiyah and Ashabiah for Economic Development in Medina) - Moh. Syarifudin; Nur Kholis (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
Islam provides fundamental sources for human development, including ukhuwah Islamiyah, ashabiah and rahmatan lil 'alamin. These concepts are strategic in developing the economy of the state.  The current article aims to analyze the economic development in Medina carried out by the Prophet Muhammad. The authors employed a qualitative method through narrative reviews of the extant literature. The study shows that before the hijrah of the Prophet, Medina was already a multicultural and heterogeneous society with many prolonged conflicts.. The Prophet devised a strategic approach to build the Medina economy and society. Ukhuwah Islamiyah was used to unify differing, often conflicting cultures, beliefs, and ethnicities to form a strong brotherhood. Ashabiah was applied to tighten the glue among society members, creating high social solidarity. Upon the perfection of Medina, the apostolate of rahmatan lil 'alamin leads to a universal, inclusive, and sustainable economic development.